The Transfer, Prevalence, Persistence, and Recovery of DNA from Body Areas in Forensic Science: A Review - Cara Woollacott; Mariya Goray; Roland A. H. van Oorschot; Duncan Taylor (Forensic Sciences)
Forensic and medical examiners are often required to sample the body of a victim (either living or deceased), or a suspect of a criminal offence, for foreign DNA. This can provide useful information when the alleged activity involves the presence of various bodily fluids such as blood, semen, and/or saliva, as well as skin contact made between a perpetrator and a victim. Optimal recovery techniques for the collection of DNA evidence, following crime-relevant skin contact, can be dependent on the surface being sampled. Additional factors to consider include the body areas typically contacted during various activities and the likelihood of non-self-DNA being present in those areas prior to contacts of interest. Therefore, an understanding of DNA transfer, prevalence, persistence, and recovery on a body can aid in the interpretation of DNA results given activity-level questions and increase the value of the findings from this type of evidence. This review aims to summarise research on DNA-TPPR concerning various human body surfaces following different types of activities. This review examines the prevalence of background DNA on different skin surfaces, the reported DNA transfer associated with different forms of contact, and how different cofounding factors can affect the persistence of DNA.